The Development of American and Japanese Colonialism in the Philippine Islands (1899-1946) Reviewed Using A Diachronic Approach - Ardi Tri Yuwono; Vengadcruz Vicaldo (Criksetra: Jurnal Pendidikan Sejarah, 2025)
Colonialism refers to the practice of a country's domination of territory and population outside its territorial boundaries. This phenomenon has resulted in significant changes in many countries around the world, including the Philippine Islands. Since the arrival of colonial powers, such as the United States and Japan, the Philippine Islands have undergone changes in social, political, and economic aspects. This research aims to explore the impact of the colonial power on social, political, and economic development in the Philippine Islands. The method used in this study is a historical method with a qualitative approach. In addition, a diachronic approach is applied to understand the history of colonialism in the Philippine Islands chronologically. The results of this study show that there are differences in the practice of colonialism between the United States and Japan in the Philippine Islands. The United States carried out colonialism in the Philippine Islands by guiding the Philippines towards a better democratic system through education. Meanwhile, the Japanese occupation of the Philippines carried out colonialism by forcing Filipinos to work forcibly in the agricultural sector.